2021
DOI: 10.3390/f12060697
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Optimization and Tradeoffs of Alternative Forest Management Scenarios in Macedonia, Greece

Abstract: Managing forests has been demonstrated to be an efficient strategy for fragmenting fuels and for reducing fire spread rates and severity. However, large-scale analyses to examine operational aspects of implementing different forest management scenarios to meet fire governance objectives are nonexistent for many Mediterranean countries. In this study we described an optimization framework to build forest management scenarios that leverages fire simulation, forest management, and tradeoff analyses for forest are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…As with the wildfire exposure in communities (Figure 6A), cumulative exposure charts highlighted the high concentration of most exposure in a reduced portion of the landscape. Previous works conducted in other fire-prone Mediterranean areas also found that most exposure was concentrated in a reduced part of the landscape [48,65]. Interestingly, most exposed areas were manageable land classes, while less than 10% corresponded to non-manageable protected land (Figure 8B).…”
Section: Wildfire Exposure In Protected Areasmentioning
confidence: 53%
See 1 more Smart Citation
“…As with the wildfire exposure in communities (Figure 6A), cumulative exposure charts highlighted the high concentration of most exposure in a reduced portion of the landscape. Previous works conducted in other fire-prone Mediterranean areas also found that most exposure was concentrated in a reduced part of the landscape [48,65]. Interestingly, most exposed areas were manageable land classes, while less than 10% corresponded to non-manageable protected land (Figure 8B).…”
Section: Wildfire Exposure In Protected Areasmentioning
confidence: 53%
“…Then, the fire spread is predicted using Rothermel's surface fire spread model [43], and fire intensity (kW m −1 ) is converted to flame length (FL) using Byram's equation [44]. The FConstMTT program has been extensively described and widely used in several fire-prone areas worldwide to model wildfire spread and behavior in large landscapes and assess wildfire exposure, transmission, and risk to valued resources and assets [26,[45][46][47][48].…”
Section: Wildfire Simulation Modelingmentioning
confidence: 99%
“…The temperate forests of southern Greece are mainly composed of species adapted to hot and dry environments, such as Pinus halepensis, Pinus brutia, and most of the evergreen broadleaves [35]. In general, plant biomass is abundant enough to sustain fire spread, mainly due to the unbalanced policy adopted by the Greek state, which heavily promotes fire suppression over sustainable forest management [36]. Therefore, the main factor limiting the extent and severity of wildfires is the moisture content of available fuels.…”
Section: Antecedent Conditions and Fuelsmentioning
confidence: 99%
“…Simulation modelling has been used for evaluating wildfire exposure and wildfire risk-mitigation strategies from the forest stand scale to the landscape, regional, and national levels (Collins et al 2011;Ager et al 2020). Fire simulation models such as FlamMap (Finney 2006) are increasingly used in the European Union to assess wildfire hazard and risk (Xofis et al 2020;Palaiologou et al 2021;Salis et al 2013), as well as the effects of fuel treatment on wildfire spread and behavior at a landscape scale (Cortes-Molino et al 2020;Molina et al 2021). FlamMap requires gridded geospatial input data on topography and fire behavior prediction (FBP) fuel types, along with weather streams.…”
Section: Introductionmentioning
confidence: 99%